La acción política frente al estigma de la violencia entre los jóvenes universitarios posconflicto: los casos de la Universidad Nacional Mayor de San Marcos y la Universidad Nacional de San Cristóbal de Huamanga - Jave, Iris; Cépeda, Mario; Uchuypoma, Diego (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
This paper explores the different way on which the internal armedconflict still affects the Peruvian universities; now, through a process of symbolic violence from many spheres like the family or the mass media. In this context, the students build new forms of political participation; the university as a space of political debate and action is seriously affected by the fear of its students to be marked by the stigma of the violence; moreover, all this is amplified by the destruction of the political system and the lack of interest on the regular ways of political participation among young students. Although, in our research we have found that university students participate in different spheres of the public life that, without being planned, cre- ates new ways of political participation: the case of the colectivos. We conclude that between the stigma —and the supposed presence of Movadef in the universities—, and the lack of institutional ways to channel their demands, the students are building a new form of political action that will be fully shaped in the future when they achieve to structure their movement and colectivos.

Este artículo explora los mecanismos por los cuales el período de violencia en el país sigue impactando las universidades, esta vez mediante la violencia simbólica expresada en formas de estigmatización desde un actor interno (la familia) y desde un actor externo (los medios de comunicación). En ese contexto, los jóvenes de esta generación construyen nuevas formas de participación política; la universidad como espacio de deliberación y de acción política uni- versitaria se ve mediada por el temor a ser señalado y estigmatizado como una consecuencia casi natural de la violencia, sin descuidar el desinterés por la política que prevalece en las últimas décadas. Pese a ello, encontramos que los jóvenes han llevado su experiencia participativa hacia nuevas formas de acción que, sin proponérselo o reconocerlo, son también plataformas políticas. Concluimos que entre el estigma —la supuesta presencia del Movadef— y la falta de canales institucionales, los universitarios se encuentran en una etapa no cohesionada pero que podría configurarse como acción colectiva.
The political action and the violence’s stigma among postconflcit universities’ students: A study in the Universidad Nacional Mayor de San Marcos and the Universidad Nacional de San Cristóbal de Huamanga
Keywords: Memoria; Estigma; Universidades; Participación; Política; https://purl.org/pe-repo/ocde/ford#5.04.03